(untitled) (Bioagro, 2025)
Grain sorghum is planted annually in Mexico on 1 427 202 ha; 55,12 % of this area corresponds to the State of Tamaulipas, mainly under rainfall conditions, with yields of 2 284 kg ha-1. The objective of this research was to identify sorghum genotypes that present high grain yield and stability, comparing the stability parameters of Eberhart and Russell and the GGE biplot model, to define the model that best describes the G x A interaction. This research was carried out with five sorghum genotypes in 14 test environments: seven irrigated and seven only with pre-sowing irrigation in Rio Bravo, Tamaulipas, during 2023. Grain yield kg·ha-1 was analyzed using the Eberhart and Russell stability parameters and the GGE biplot model. The results show that when the Eberhart and Russell model was used, the P83G19 hybrid was identified as a consistent, stable genotype, with a grain yield 1.23 % higher than the general average, and the ADV-G3247 hybrid and the RB-Williams variety were identified as consistent genotypes, which respond better in good environments, with grain yields 7.31 and 0.4 % higher than the general average, respectively. When the GGE biplot model was used, the P83G19 hybrid exhibited stability and good grain yield. The two stability analysis models consistently identified stable and high-yielding genotypes, determining the accuracy of both methods and their usefulness in understanding the Genotype x Environment (G x E) interaction to identify genotypes with broad or specific adaptation.